2015
DOI: 10.1155/2015/874067
|View full text |Cite
|
Sign up to set email alerts
|

Medication Lists and Brown Bag Reviews: Potential Positive and Negative Impacts on Patients Beliefs about Their Medicine

Abstract: Introduction. Medication lists and structured medication counselling (SMC) including “brown bag reviews” (BBR) are important instruments for medication safety. The aim of this study was to explore whether patients' use of a medication list is associated with their beliefs about their medicine and their memory of SMC. Methods. Baseline data of 344 patients enrolled into the “Polypharmacy in Multimorbid Patients study” were analysed. Linear regression models were calculated for the “specific necessity subscale” … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…One study reported quantitatively that patients have less concerns (p<0.01) and increased perceived necessity of their medication (p<0.01) when they possess a comprehensive medication chart. 39 It further gave patients a more active role 40 and made them feel more responsible for their medical treatment. 5 34…”
Section: Resultsmentioning
confidence: 99%
“…One study reported quantitatively that patients have less concerns (p<0.01) and increased perceived necessity of their medication (p<0.01) when they possess a comprehensive medication chart. 39 It further gave patients a more active role 40 and made them feel more responsible for their medical treatment. 5 34…”
Section: Resultsmentioning
confidence: 99%
“…In a German study among elderly patients with multiple morbidities and polypharmacy, regular receipt of an updated medication list was associated with a higher perceived necessity to take one's specific medication. In addition, patients who found their medication list comprehensive had less concerns about their individual medication [20].…”
Section: Discussionmentioning
confidence: 99%
“…Another aspect that influences medication adherence is patients' beliefs about medicines [18][19][20], though study outcomes are inconsistent [18,19,21]. In a study by Jäger et al [22] the authors concluded that minimizing concerns in nonadherent, more worried patients might be as important as raising awareness in those less bothered.…”
Section: The Role Of Medication Nonadherence and Beliefs About Medicinesmentioning
confidence: 99%